HYDROMECHANICAL TECHNOLOGY OF TUBULAR DRAINAGE NETWORK PURIFICATION - Alexander V. Mikheyev (Advanced Engineering Research)
Advanced technology of tubular drainage network purification by sprinkler, and  analytic dependences that adequately describe purification processes of culverts and   transfer of drainage rinser including water-supply hose are presented.